Why Non-accelerated Filers Voluntarily Comply with SOX 404b? - Liu, Zhenfeng; Cheng, Yun; Liu, Ruonan (International Journal of Accounting & Finance Review, 2020)
This paper investigates the managers’ incentives to voluntarily comply with SOX 404b and the determinants of firms who voluntarily disclose SOX 404b internal control over financial reporting assessment. We find that voluntary SOX 404b reporting non-accelerated filers are more likely to receive effective internal control over financial reporting opinion than accelerated filers and large accelerated filers. We find that voluntary SOX 404b reporting non-accelerated filers are more likely to hire Big Four as independent auditors than non-SOX 404b reporting non-accelerated filers. We also predict and found substantially sufficient cases where non-accelerated filers which used to be, or ex-post became accelerated filers or large accelerated filers, and non-accelerated filers with parent companies complying with SOX 404b are motivated to voluntarily comply with SOX 404b.